High-dose third-generation EGFR-TKIs combined with intrathecal pemetrexed in advanced EGFR-mutant NSCLC with leptomeningeal metastases following EGFR-TKI therapy - Shugui Wu; Zhengang Qiu; Huaqiu Shi; Wei Yu; Linfang Liu; Longqiu Wu; Wenjuan Zhong (BMC Cancer)
Abstract Background Leptomeningeal metastasis in EGFR-mutant (EGFRm) non-small-cell lung cancer (NSCLC) is a severe complication particularly prevalent in patients who have previously been treated with EGFR-tyrosine kinase inhibitors (EGFR-TKIs). However, an optimal treatment strategy for dealing with leptomeningeal metastases in patients with NSCLC has yet to be developed. High-dose EGFR-TKIs in combination with intrathecal chemotherapy may offer a promising treatment strategy for this patient population. Methods We retrospectively identified patients with EGFRm NSCLC who were diagnosed at the First Affiliated Hospital of Gannan Medical University between January 1, 2018, and December 31, 2023. All patients developed leptomeningeal metastases after EGFR-TKI treatment and then received intrathecal pemetrexed chemotherapy in combination with high-dose third-generation EGFR-TKIs (osimertinib 160 mg/day, furmonertinib 160 mg/day, or aumolertinib 165 mg/day), with or without other therapies. Intracranial response, intracranial progression-free survival, overall survival, and safety were evaluated. Results Twenty-three patients were enrolled. The median follow-up was 20 months (range, 2–35). The median number of intrathecal pemetrexed injections was 4 (range, 2–26). The intracranial symptom relief rate was 91.3% (21/23), intracranial disease control rate was 86.96% (20/23), median intracranial progression-free survival was 10 months (95% CI, 1.52–18.48), and median overall survival was 12 months (95% CI, 5.43–18.57). The most frequent adverse event was myelosuppression (n = 10, 43.48%), which was limited to grade 1 or 2. Two grade 3 adverse events were observed, including one case of interstitial pneumonia and one case of diarrhea. Univariate and multivariate analyses demonstrated that the combination of bevacizumab and an Eastern Cooperative Oncology Group performance status of ≤ 1 were favorable prognostic factors for survival. Conclusions High-dose third-generation EGFR-TKIs combined with pemetrexed intrathecal chemotherapy demonstrated a high rate of intracranial symptom relief and manageable safety in patients with EGFRm NSCLC who developed leptomeningeal metastases after previous EGFR-TKI therapy.